Frequency of occurrence of k-casein genotypes and their effect on the milk productivity of Kholmogory cows - N. A. Khudyakova; I. S. Kozhevnikova; E. N. Shchipakova; A. A. Kondakova; M. S. Kalmykova; Н. А. Худякова; И. С. Кожевникова; Е. Н. Щипакова; А. А. Кондакова; М. С. Калмыкова (FARC North-East, 2024)
To increase the volume of domestic dairy products, it is necessary to use modern breeding methods and select animals with high genetic potential. To determine the genetic potential of animals, molecular genetic markers are used, which make it possible to study how a specific genetic variant or combination of genes affects the desired trait. The purpose of the study is to identify the frequency of occurrence of allelic variants of the kappa-casein gene (CSN3) in Kholmogory cows and their relationship with milk production. The object of the study is 195 cows. To determine the genotypes of kappa-casein, the method of polymerase chain reaction of restriction fragment length polymorphism was used. The research was carried out in 2023 on the basis of JSC Kholmogorsky Breeding Plant (Arkhangelsk region). Results: in the studied herd, allele A of the kappacasein gene dominates – 80 %, respectively, allele B was 20 %. The predominant genotype is AA – 63.08 % (n = 123), the less common genotype AB is 33.33 % (n = 65), the least common genotype is BB – 3.59 % (n = 7). To assess milk productivity and milk quality in cows with different CSN3 genotypes, productivity indicators for the last completed lactation were compared. The total number of cows with completed lactation in the study sample was 130 heads, of which: 37 cows were first-calf heifers, 6 cows in the second lactation and 87 cows in the third or more lactation. In total, according to the comparison results, cows with the BB genotype had the highest indicators: milk yield – 6916±275 kg, mass fraction of fat – 4.14±0.22 %, mass fraction of protein – 3.16±0.07 %, amount of milk fat – 286±19 kg, amount of milk protein – 219±12 kg. Thus, the desired genotype for the CSN3 gene is BB. At the moment, there are very few carriers of this gene, so it is necessary to carry out selection and breeding work aimed at increasing their numbers. Для повышения объемов отечественной молочной продукции необходимо использовать современные методы селекции и отбор животных проводить с ...